Constituents of Cannabis Sativa - Reyes-Parada, M (Springer, 2021)
Cannabis sativa L. is a psychoactive plant that contains more than 500 chemical components. Even though the consumption (in the form of marijuana, hashish, or hashish oil) for recreational purposes, is the most popular way of using the plant, the knowledge of its components has also led to classify Cannabis sativa L. is a plant with medicinal or therapeutical use. Several comprehensive reviews have already been published focused on the chemical composition of Cannabis sativa. In this chapter, we will summarize relevant information about those components, which may help to understand its biological actions that will be described in the following chapters. © 2021, Springer Nature Switzerland AG.